Ultrasound versus placebo for pain reduction in patients with knee osteoarthritis: Critical appraisal of a meta-analysis - Raúl Aguilera Eguía; Héctor Gutiérrez Espinoza (Medwave, 2012)
This CAT (Critically Appraised Topics) sought to answer the following question: In adult patients with mild knee osteoarthritis, can therapeutic ultrasound decrease pain compared to placebo? Analysis was structured in four parts: patient, intervention, comparison and outcome. The aim was to test validity, results and applicability of the effectiveness in reducing pain in patients with mild knee osteoarthritis from the article "Efficacy of ultrasound therapy for the management of knee osteoarthritis: a systematic review with meta-analysis. Osteoarthritis Cartilage".